Is well-being U-shaped over the life cycle? - David G. Blanchflower; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2007)
We explore the idea that happiness and psychological well-being are U-shaped in age. The main difficulty with this argument is that there are likely to be omitted cohort effects (earlier generations may have been born in, say, particularly good or bad times). First, using data on 500,000 randomly sampled Americans and West Europeans, the paper designs a test that controls for cohort effects. A robust U-shape is found. Ceteris paribus, a typical individual's well-being reaches its minimum - on both sides of the Atlantic and for both males and females - in middle age. We demonstrate this with a quadratic structure and non-parametric forms. Second, some evidence is presented for a U-shape in developing countries and the East European nations. Third, using measures that are closer to psychiatric scores, we document a comparable well-being curve across the life course in two other data sets: (i) in GHQ-N6 mental health levels for a sample of 16,000 Europeans, and (ii) in reported depression and anxiety among approximately 1 million U.K. citizens. Fourth, we document occasional apparent exceptions, particularly in developing nations, to the U-shape. Fifth, we note that American male birth cohorts seem to have become progressively less happy with their lives. Our paper's results are based on regression equations in which other influences, such as demographic variables and income, are held constant.
Keywords: 330; Happiness; aging; well-being; GHQ; cohorts; Lebenszufriedenheit; Altersgruppe; Lebenszyklus; USA; Europa